1979
DOI: 10.1079/bjn19790008
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional effects of field bean (Vicia fabaL.) proteinase inhibitors fed to rats

Abstract: I . Weanling rats were fed on purified-casein diets containing active and inactive (autoclaved) field bean (Mcia faba L.) proteinase inhibitors (PI) a t levels of 1.25, 25, 5.0 and 10 g/kg. Diets containing raw-and autoclaved-field-bean meal (FBM) were also given. The body-weight gain, protein efficiency ratio (PER); i.e. the ratio of the live weight gain in g/g of protein consumed and apparent nitrogen digestibility were determined 7, 14 and 21 d after the start of the trial. 2.Significant growth depression (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 20 publications
(11 reference statements)
4
15
0
Order By: Relevance
“…The inclusion of high amounts of faba beans (Vicia faba L.) in diets has been reported to have a detrimental effect on the performance of rats (Marquardt et at, 1974;Abbey et at, 1979;Moseley & Griffiths, 1979) and chickens (Guillaume, 1977;Marquardt & Ward, 1979;Rubio et al, 1990). This has generally been attributed to the presence in the seeds of various antinutritive/toxic substances.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of high amounts of faba beans (Vicia faba L.) in diets has been reported to have a detrimental effect on the performance of rats (Marquardt et at, 1974;Abbey et at, 1979;Moseley & Griffiths, 1979) and chickens (Guillaume, 1977;Marquardt & Ward, 1979;Rubio et al, 1990). This has generally been attributed to the presence in the seeds of various antinutritive/toxic substances.…”
Section: Introductionmentioning
confidence: 99%
“…They are mostly derivatives and/or isomers of flavones, isoflavones, flavonols, catechins and phenolic acids, and possess diverse pharmacological properties such as antioxidant, antiapoptosis, antiaging and anticarcinogenic [1]. Phenolic monomers are potent inhibitors of plant [3] and mammalian [4][5][6] enzymes. Phenolic monomers are potent inhibitors of plant [3] and mammalian [4][5][6] enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…23, 27], Many investigators have reported the factors in volved in this phenomenon [1,10,19] and a hypothesis that growth inhibition is largely due to the presence of trypsin or proteinase inhibitors, present in an active form, in raw legumes has been proposed [ 18,24], It has been reported that raw legumes have an influence on the urinary nitrogenous compounds as well as amino acid-degrading enzymes [7]. It has been observed in this lab oratory that green gram (Phaseolus aureus Roxb).…”
Section: Introductionmentioning
confidence: 99%